De novo histoid leprosy in an immunocompetent male: a rare case report from North east India - Kalvit, Kushal R. (International Journal of Scientific Reports, 2019)
Histoid leprosy is a rare form of lepromatous (multibacillary) leprosy. This form of leprosy is fairly common in patients on dapsone monotherapy and irregular treatment. Sometimes it can arise de novo as well. Very few cases have been reported in immunocompetent individuals from India. I report a case of de novo histoid leprosy in a 22 year old male from north east India.